Pt–Co Alloy Nanoparticles on a γ‐Al2O3 Support: Synergistic Effect between Isolated Electron‐Rich Pt and Co for Automotive Exhaust Purification. Issue 5 (23rd January 2019) - Sato, Katsutoshi; Ito, Ayano; Tomonaga, Hiroyuki; Kanematsu, Homare; Wada, Yuichiro; Asakura, Hiroyuki; Hosokawa, Saburo; Tanaka, Tsunehiro; Toriyama, Takaaki; Yamamoto, Tomokazu; Matsumura, Syo; Nagaoka, Katsutoshi
Abstract: There is interest in minimizing or eliminating the use of Pt in catalysts by replacing it with more widely abundant and cost‐effective elements. The alloying of Pt with non‐noble metals is a potential strategy for reducing Pt use because interactions between Pt and non‐noble metals can modify the catalyst structure and electronic properties. Here, a γ‐Al2 O3 ‐supported bimetallic catalyst [Pt(0.1)Co(1)/Al2 O3 ] was prepared which contained 0.1 wt % Pt and 1 wt % Co and thus featured an extremely low Pt : Co ratio (<1 : 30 mol/mol). The Pt and Co in this catalyst formed alloy nanoparticles in which isolated electron‐rich Pt atoms were present on the nanoparticle surface. The activity of this Pt(0.1)Co(1)/Al2 O3 catalyst for the purification of automotive exhaust was comparable to the activities of 0.3 and 0.5 wt % Pt/γ‐Al2 O3 catalysts. Electron‐rich Pt and metallic Co promoted activation of NO x and oxidization of CO and hydrocarbons, respectively. This strategy of tuning the surrounding structure and electronic state of a noble metal by alloying it with an excess of a non‐noble metal will enable reduced noble metal use in catalysts for exhaust purification and other environmentally important reactions. Abstract : Tuning the surrounding structure and electronic state of Pt by alloying it with an excess of Co is a potential strategy for reducing Pt use. The isolated electron‐rich Pt atoms present on the Pt−Co alloy nanoparticle surface play an important role in NO x reduction(see Figure). Alloying Pt with Co could facilitate a 60 %–80 % reduction in the use of Pt in catalyst for exhaust purification.